Exercise Management for Young People With Type 1 Diabetes: A Structured Approach to the Exercise Consultation - Chetty, Tarini; Shetty, Vinutha; Fournier, Paul Albert; Adolfsson, Peter; Jones, Timothy William; Davis, Elizabeth Ann (Frontiers in Endocrinology, 2019)
Regular physical activity during childhood is important for optimal physical and psychological development. For individuals with Type 1 Diabetes (T1D), physical activity offers many health benefits including improved glycemic control, cardiovascular function, blood lipid profiles and psychological well-being. Despite these benefits, many young people with T1D do not meet physical activity recommendations. Barriers to engaging in a physically active lifestyle include fear of hypoglycemia, as well as insufficient knowledge in managing diabetes around exercise in both individuals and health care professionals. Diabetes and exercise management is complex, and many factors can influence an individual’s glycemic response to exercise. Consequently, it can be challenging for health care practitioners to advise young people with T1D how to approach exercise management in a busy clinic setting. This review provides a structured approach to the child/adolescent exercise consultation, based on a framework of questions, to assist the health care professional in formulating person-specific exercise management plans for young people with T1D.